Nurse's knowledge of neuropathic pain - Ali Yavuz Karahan; Seher Kucuksarac; Neslihan Soran; Banu Ordahan; Levent Tekin; Aynur Basaran (MDPI AG, 2014)
The aim of our study was to determine the levels of information and awareness of the nurses who work on neuropathic pain in the departments of physical medicine and rehabilitation, neurology and neurosurgery. A total of 60 nurses (20 per each department) who work in the physical medicine and rehabilitation, neurology and neurosurgery departments of Beyhekim State Hospital of Konya in Turkey took part in the study. The level of information and awareness of the nurses on neuropathic pain were assessed via a questionnaire prepared by specialists in the light of recent literature. The questionnaire was composed of 30 questions including the definition, symptoms, treatment and management of neuropathic pain. None of 60 nurses participating in the study were given any previous in-service training on neuropathic pain. According to the assessments, 80% of nurses (48) were found not to have sufficient knowledge about definition of neuropathic pain; 83.3% (50) about diseases causing neuropathic pain; 83.3% (50) about symptoms of neuropathic pain; and 90% (54) about management of neuropathic pain. The findings obtained from the nurses of these three departments showed no statistically significant relation. Our findings indicated that the knowledge of participants' about neuropathic pain who work in these three departments seriously lack of information. Informing nurses about neuropathic pain during in-service training will be an important step towards improving the quality of services provided.